Anti-carbamylated protein antibodies in systemic lupus erythematosus patients with articular involvement. (January 2018) - Massaro, L; Ceccarelli, F; Colasanti, T; Pendolino, M; Perricone, C; Cipriano, E; Natalucci, F; Capalbo, G; Lucchetti, R; Pecani, A; Vomero, M; Mancini, R; et al.
Objective: Several studies have evaluated the prevalence of rheumatoid factor (RF) and anti-citrullinated proteins antibodies (ACPA) in systemic lupus erythematosus (SLE) patients but no data are available on the anti-carbamylated proteins (anti-CarP), a new biomarker for rheumatoid arthritis (RA). We evaluated the anti-CarP prevalence in SLE patients with joint involvement and the associations with different phenotypes. Methods: Seventy-eight SLE patients with joint involvement were enrolled (F/M 73/5; mean ± SD age 47.6 ± 11.2 years; mean ± SD disease duration 214.3 ± 115.6 months). As control groups, we evaluated SLE patients without joint manifestations ( N  = 15), RA ( N  = 78) and healthy individuals (HS, N  = 98). Anti-CarP were assessed by home-made ELISA in all patients and controls, RF and ACPA in SLE patients with joint involvement (commercial ELISA kit). Results: The prevalence of anti-CarP in SLE patients with joint involvement was similar to RA ( p  = NS) and significantly higher compared with SLE without joint involvement and HS ( p  < 0.0001, p  < 0.0001, respectively). Four patients were positive for all three antibodies: seventy-five percent of these showed Jaccoud arthropathy. Fourty-five percent of ACPA-ve/RF-ve patients were anti-CarP + ve. Conclusions: The evaluation of anti-CarP in SLE joint involvement demonstrated a prevalence of almost 50%, similar to RA and significantly higher than SLE without joint involvement and HS.